Long-Term Longitudinal Stability of Kidney Filtration Marker Measurements: Implications for Epidemiological Studies and Clinical Care. (30th November 2020) - Karger, Amy B; Eckfeldt, John H; Rynders, Gregory P; Chaudhari, Juhi; Miao, Shiyuan; Van Lente, Frederick; Coresh, Josef; Levey, Andrew S; Inker, Lesley A
Abstract: Background: Establishment and improvement of glomerular filtration rate estimating equations requires accurate and precise laboratory measurement procedures (MPs) for filtration markers. The Advanced Research and Diagnostic Laboratory (ARDL) at the University of Minnesota, which has served as the central laboratory for the Chronic Kidney Disease Epidemiology Collaboration since 2009, has implemented several quality assurance measures to monitor the accuracy and stability of filtration marker assays over time. Methods: To assess longitudinal stability for filtration marker assays, a 40-sample calibration panel was created using pooled serum, divided into multiple frozen aliquots stored at −80 °C. ARDL monitored 4 markers—creatinine, cystatin C, beta-2-microglobulin (B2M) and beta-trace protein—measuring 15 calibration panel aliquots from 2009 to 2019. Initial target values were established using the mean of the first 3 measurements performed in 2009–10, and differences from target were monitored over time. New MPs for cystatin C and B2M were added in 2012, with target values established using the first measurement. Results: The mean percentage difference from mean target values across time was <2% for all original MPs (−0.59% for creatinine; −0.94% for cystatin C; −0.82% for B2M; 1.24% for beta-trace protein). Conclusions: Close monitoring of filtration marker trends with a calibration panel at ARDL demonstrates remarkable long-term stability of the MPs. Routine use of a calibration panel for both research studies and clinical care is recommended for filtration markers where longitudinal monitoring is important to detect analytical biases, which can mask or confound true clinical trends in patients.